TRANSFORMATION INTO THE â€œGODâ€: STUDY OF CRITICâ€“ELABORATIVE AXIOLOGY OF ISLAMIC EDUCATION WITH PHILOSOPHICAL SUFISM - Umiarso, Umiarso (Badan Litbang dan Diklat Kementerian Agama RI, 2019)
AbstractEmbody an al-insan al-kamil is the ultimate aim of Islamic Education and philosophical Sufism. This human construction can be emerged through education that internalizes divine natures in the subject of education. Therefore, between Islamic educational philosophic has dialectical relation to embody human into â€œGodâ€. Therefore, this article focused on the construction of Islamic education in realizing al-insan al-kamil (a complete man) which has similarities with the goals of philosophical Sufism. The aim is to analyze and understand the construction of human transformation efforts into